Do African American adolescents internalize direct online discrimination? Moderating effects of vicarious online discrimination, parental technological attitudes, and racial identity centrality - Tao, Chun; Scott, Kimberly A. (Frontiers in Psychology, 2022)
African American adolescents have become more active users of digital media, which may increasingly expose them to direct online discrimination based on their racial and gender identities. Despite well-documented impacts of offline discrimination, our understanding of if and how direct online discrimination affects African American adolescents similarly remains limited. Guided by intersectional and ecological frameworks, we examined the association between direct online discrimination and internalized computing stereotypes in African American adolescents. Further, we explored the moderating effects of systemic and individual factors - vicarious online discrimination, parental technological attitudes, and racial identity centrality – on this association by adolescent gender. Utilizing data from 1041 African American parent-adolescent dyads, we found a positive association between adolescents’ direct online discrimination and internalized computing stereotypes. Surprisingly, greater vicarious online discrimination mitigated this association for both male and female adolescents. Further, parental technological attitudes and racial identity centrality mitigated this association only for female but not male adolescents. Our findings highlight the importance of understanding the impact of media on adolescents’ online experiences from intersectional and systemic perspectives. We discuss the implications for prospective research and educational programs focused on African American adolescents’ digital media use and online experiences.